2019
DOI: 10.1002/cam4.2278
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase 4 inhibitors as novel agents in improving survival in diabetic patients with colorectal cancer and lung cancer: A Surveillance Epidemiology and Endpoint Research Medicare study

Abstract: Background Dipeptidyl peptidase 4 (DPP4) is a cell surface protein that can act as a tumor suppressor or activator, depending upon the level of expression and interaction with the microenvironment and chemokines. DPP4 inhibitors are used to treat diabetes. Methods We conducted this Surveillance Epidemiology and Endpoint Research‐Medicare database study to evaluate the role of DPP4 inhibitors on the overall survival (OS) of diabetic patients diagnosed with colorectal (CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 17 publications
(39 reference statements)
1
36
1
1
Order By: Relevance
“…The study showed significant advantage in progression-free survival and a positive trend in overall survival (OS); however, OS did not reach the level of statistical significance likely due to small sample size (12). To further clarify the role of DPP4i, we conducted a SEER (Surveillance Epidemiology and Endpoint Research)-Medicare analysis of colorectal cancer and lung cancer patients, which also showed a similar trend toward beneficial effects associated with CD26/DPP4 inhibition (13). Apart from colorectal and lung cancer, CD26/DPP4 protein is well-expressed in prostate cancer cells, while its expression in pancreatic or breast cancer cells is relatively lower (1,2,14).…”
Section: Introductionmentioning
confidence: 99%
“…The study showed significant advantage in progression-free survival and a positive trend in overall survival (OS); however, OS did not reach the level of statistical significance likely due to small sample size (12). To further clarify the role of DPP4i, we conducted a SEER (Surveillance Epidemiology and Endpoint Research)-Medicare analysis of colorectal cancer and lung cancer patients, which also showed a similar trend toward beneficial effects associated with CD26/DPP4 inhibition (13). Apart from colorectal and lung cancer, CD26/DPP4 protein is well-expressed in prostate cancer cells, while its expression in pancreatic or breast cancer cells is relatively lower (1,2,14).…”
Section: Introductionmentioning
confidence: 99%
“…DPP4 preferentially cleaves after proline or alanine in the penultimate position from the N-terminus of polypeptides. DPP4 cleavage of the incretin peptides, glucagon-like peptide-1 (GLP-1) and gastric inhibitory polypeptide (GIP), have led to the development of DPP4 selective inhibitors as a successful type 2 diabetes mellitus (T2DM) therapy [4,[13][14][15][16]. The outer surface of the propeller domain of DPP4 contains binding sites for other proteins, most notably the non-catalytic binding with human adenosine deaminase (ADA) [6,8,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, DPP-4 can act either as a tumor activator or suppressor depending on paracrine signals, the microenvironment, and molecular interactions [42,43]. The pharmacological inhibition of DPP-4 in lung cancer patients showed improved overall survival, which was attributed to the effect of DPP-4 inhibition on tumor immunoregulation [44,45]. Information on the role of DPP-4/CD26 in tumor biology can be inferred from either transgenic animals that lack DPP-4 or its pharmacological inhibition.…”
Section: Dpp-4 and Lung Cancermentioning
confidence: 99%